Studi Kasus Dinamika Psikologis Pasien dengan Gangguan Mental Psikotik Skizoafektif - Santi Tri Wintari (Psyche 165 Journal, 2020)
This study aims to describe the psychological dynamics and factors that cause one schizophrenic spectrum disorder that is schizoaffective for the symptoms of schizophrenia and affective disorders that stand out at the same time. This research is a qualitative case study with one participant, Joko who is diagnosed with schizoaffective disorder. The examination used interviews, observation, and several psychological tests. The results show that there are internal factors such as personality, coping skills, genetic vulnerability and external factors such as social support and unfulfilled affection and stressors as triggers that contribute to schizoaffective disorders. The results of the study can be a reference to prevent schizoaffective disorders through psychoeducation to families and help people with schizoaffective disorders by providing interventions to train emotional regulation and coping skills.